2016
DOI: 10.3892/ol.2016.5508
|View full text |Cite
|
Sign up to set email alerts
|

Danshensu, a major water-soluble component of Salvia miltiorrhiza, enhances the radioresponse for Lewis Lung Carcinoma xenografts in mice

Abstract: The molecule 3-(3,4-dihydroxyphenyl)-2-hydroxypropanoic acid (danshensu), a herbal preparation used in traditional Chinese medicine, has been found to possess potential antitumor and anti-angiogenesis effects. The aim of the present study was to investigate the efficacy of the combination of radiation therapy (RT) with danshensu in the treatment of Lewis lung carcinoma (LLC) xenografts, whilst exploring and evaluating the mechanism involved. In total, 8-week old female C57BL/6J mice were randomly assigned into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…Some natural compounds such as curcumin, quercetin, genistein, (Nicholson et al., 1995) danshsensu, wortmannin, and so on, are reported for inducing radiosensitization in cancer cells (Cao et al., 2017; Javvadi, Segan, Tuttle, & Koumenis, 2008; Lagerweij et al., 2016; Ortiz, Lopez, Burguillos, Edreira, & Pinero, 2004; Tang et al., 2018). Natural products owing to their antioxidant and immune‐enhancing effects may have improved effects as biological and radiation protectors for normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some natural compounds such as curcumin, quercetin, genistein, (Nicholson et al., 1995) danshsensu, wortmannin, and so on, are reported for inducing radiosensitization in cancer cells (Cao et al., 2017; Javvadi, Segan, Tuttle, & Koumenis, 2008; Lagerweij et al., 2016; Ortiz, Lopez, Burguillos, Edreira, & Pinero, 2004; Tang et al., 2018). Natural products owing to their antioxidant and immune‐enhancing effects may have improved effects as biological and radiation protectors for normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oil from another member Curcuma zedoaria , a widely used “Hua Yu Tong Luo” herb (function to dissipate blood stasis and free the collateral vessels), presented the anti-angiogenic activity, which therefore contributed to suppressing melanoma growth and lung metastasis [ 26 ]. A recent study suggested that Danshensu, a major water-soluble compound from Salvia miltiorrhiza , could improve microcirculation and remodel tumor vasculature, thereby enhancing the radioresponse for Lewis lung carcinoma xenografts in mice [ 27 ]. The aforementioned researchers revealed the anti-angiogenesis properties of several herbs from WPX.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that natural products can sensitize cancer cells to radiation therapy [ 23 , 24 ]. The mechanisms by which the natural components synergize with IR to facilitate cancer cell killing are usually by enhancing apoptosis, affecting the cell cycle, and/or attenuating angiogenesis [ 25 29 ]. In this study, we demonstrated that CMR, a type of Diels–Alder adduct from Mulberry leaves, enhances the radiosensitivity of NSCLC cells by inducing paraptosis.…”
Section: Discussionmentioning
confidence: 99%